INVENTARISASI TANAMAN OBAT UNTUK PENYAKIT HIPERTENSI PADA MASYARAKAT KECAMATAN BAREBBO, KABUPATEN BONE, PROVINSI SULAWESI SELATAN - Irma Santi; Rezki Amriati Syarif; Nitya Kusumayanti (As-Syifaa Jurnal Farmasi, 2022)
Inventory of medicinal plants is an activity to collect data related to the types of medicinal plants in an area or region. People in Barebbo District still use plants as traditional medicines to treat various diseases, one of which is hypertension. Hypertension is ranked first in the 10 cases of the most common disease suffered by the community in Barebbo District. This study was conducted with the aim of collecting data on medicinal plants used by the community in Barebbo District and how to use these plants for the treatment of hypertension. This research was conducted using the snowball sampling method and the respondents were obtained based on key-informant references. From this study, it was found that there were 21 species of plants used by the community in Barebbo District to treat hypertension and Apiaceae family was the most widely used. The people in Barebbo District utilized leaves, tubers, fruit, water, rhizomes, seeds, stems and herbs. They mostly used the plant by drinking it 1-2 times a day. Besides, they cultivated these plants by boiling, brewing, squeezing, and also consuming them directly.